2019
DOI: 10.47895/amp.v53i5.91
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Oral Mucosal Lesions in Geriatric Patients in Universitas Airlangga Dental Hospital

Abstract: Background. Population aged 60 years old and above are growing in number; a fact that will have an impact on general and oral health in the future. Oral health is often overlooked in the management of geriatric patients but it is vital to have a knowledged-based practice in order to increase the quality of life of elderly patients. Objective. The purpose of this study is to determine the number and types of oral mucosal lesions in geriatric patients who come to the Universitas Airlangga Dental Hospital.&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 6 publications
0
12
0
2
Order By: Relevance
“…This was similar to the results of 55.56% in research conducted by Mahdani et al in 2018. 4 Second highest lesion with a 16% rate was sublingual varicosities. Sublingual varicosities are normal variations that are usually in elderly patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This was similar to the results of 55.56% in research conducted by Mahdani et al in 2018. 4 Second highest lesion with a 16% rate was sublingual varicosities. Sublingual varicosities are normal variations that are usually in elderly patients.…”
Section: Discussionmentioning
confidence: 98%
“…7 An elderly patient can more easily experience coated tongue than young patients. 4,6 Moreover, changes in diet and physiological function decline in elderly patients. 11 According to Mosafarri et al, the more a person ages, there is a significant decrease in the Multi Performance Score.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another research conducted in Surabaya, Indonesia, showed that the normal variances of the mucosa with higher prevalence in the elderly are coated tongue, fissured tongue and lingual varices. 5 These conditions can affect daily activities, including mastication, swallowing, and talking, as well as cause symptoms such as xerostomia, halitosis, or dysesthesia. 6 It is important to distinguish between normal aging processes and pathological conditions in the elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…Assim como, a Organização Mundial de Saúde (OMS) define que os idosos, em países desenvolvidos, tem 60 anos ou mais, já em países subdesenvolvidos é a pessoa com idade igual a 65 anos ou superior. Em que a OMS, classifica o envelhecimento agrupando os que estão entre 60-74 anos (idosos), 75-90 (anciãos) e mais de 90 anos (velhice extrema) [1][2][3] O envelhecimento populacional é um fenômeno mundial que está acontecendo progressivamente, contudo em alguns países esse processo está muito acelerado. Por exemplo, a França demorou 150 anos para que os indivíduos de 60 anos ou mais passassem de 10% a 20% da representatividade total demográfica, enquanto que países como China e Brasil terão o mesmo resultado em 20 anos (2000-2020; 2020-2040 respectivamente) 4 .…”
Section: Introductionunclassified
“…Consoante a isso, sua resposta imunológica também está deficitária, o indivíduo está mais vulnerável a colonização de microrganismos, principalmente fúngico, e como sua capacidade de defesa e reparação não está adequada, a superfície epitelial se torna sujeita a traumas mecânicos. Tanto mudanças normais da idade quanto fatores patológicos podem influenciar no desenvolvimento de lesões bucais 3,[12][13][14][15] .…”
Section: Introductionunclassified